2011
DOI: 10.1126/scitranslmed.3002097
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac AAV9-S100A1 Gene Therapy Rescues Post-Ischemic Heart Failure in a Preclinical Large Animal Model

Abstract: As a prerequisite to clinical application, we determined the long-term therapeutic effectiveness and safety of adeno-associated viral (AAV) S100A1 gene therapy in a preclinical, large animal model of heart failure. S100A1, a positive inotropic regulator of myocardial contractility, becomes depleted in failing cardiomyocytes in humans and various animal models, and myocardial-targeted S100A1 gene transfer rescues cardiac contractile function by restoring sarcoplasmic reticulum calcium Ca2+ handling in acutely a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
159
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(173 citation statements)
references
References 51 publications
10
159
0
Order By: Relevance
“…Furthermore, S100A1 treatment was able to reconstitute cytosolic and SR Ca 2+ cycling as well as energy homeostasis in isolated CM. 66 This study demonstrated feasibility and safety of AAV9-S100A1 gene therapy in a pre-clinical model of HF and these results present a strong rational to support further translation into a first clinical trail of S100A1 gene therapy for human end-stage HF.…”
Section: Proof-of-concept For S100a1 Gene Therapysupporting
confidence: 52%
See 1 more Smart Citation
“…Furthermore, S100A1 treatment was able to reconstitute cytosolic and SR Ca 2+ cycling as well as energy homeostasis in isolated CM. 66 This study demonstrated feasibility and safety of AAV9-S100A1 gene therapy in a pre-clinical model of HF and these results present a strong rational to support further translation into a first clinical trail of S100A1 gene therapy for human end-stage HF.…”
Section: Proof-of-concept For S100a1 Gene Therapysupporting
confidence: 52%
“…65 Domestic pigs are widely accepted as a pre-clinical model for cardiac research. In the latest study by Pleger et al, 66 MI was induced by balloon occlusion of the left circumflex coronary artery for 2 h. AAV9-S100A1 cardiac-restricted gene therapy was performed 2 weeks later via the anterior vein into the left ventricular remote myocardium. After 14 weeks, gene transfer resulted in cardiac restricted gene expression without any signs of extra-cardiac expression analyzed by AAV-luciferase expression.…”
Section: Proof-of-concept For S100a1 Gene Therapymentioning
confidence: 99%
“…We have recently completed a study in a preclinical large animal model (farm pigs) aimed at investigating whether GRK2 inhibition with the bARKct represents a feasible therapeutic approach for HF. 46 In this study, taking advantage of our established ischemic cardiomyopathy pig model, 52 we found that AAV6-bARKct delivery via retrograde coronary venous perfusion could improve left ventricular dysfunction, and this therapeutic effect was accompanied by normalization of neurohormonal signaling and repression of adverse cardiac remodeling and fetal gene expression. 46 This study is important as the pig HF model more closely reflects human pathophysiology and is thus a prerequisite for planning clinical testing (Figure 3).…”
Section: Targeting Grk2 By Gene Therapy For Hf J Reinkober Et Almentioning
confidence: 76%
“…Gene transfer of S100A1, another calcium regulating protein, which impacts not only SERCA2a but also ryanodine receptors, was conducted in a pig myocardial infarction model. 83 Significant improvement of cardiac function over control pigs was accompanied by normalized cardiomyocyte Ca 2+ cycling 12 weeks after gene transfer. Other promising targets of calcium cycling proteins, such as inhibitor-1, protein phosphatase 1 and parvalbumin are also reported from rodent studies, and further studies are anticipated in large animals to translate these therapies into clinical studies.…”
Section: Calcium Cycling Proteinsmentioning
confidence: 95%
“…In fact, most of the large animal studies that targeted calcium cycling used adenoassociated virus to demonstrate the chronic efficacy. [5][6][7]23,25,79,83 The importance of this vector is growing with the increasing attention to treat heart failure with gene therapy.…”
Section: Non-viral Vectorsmentioning
confidence: 99%